Peningkatan Motivasi Berwirausaha melalui Sosialisasi Peluang Bisnis Sektor Jasa bagi Santriwati di Pondok Pesantren - Yudi Tusri; Anton Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Economic independence for Islamic boarding school graduates remains a challenge amidst competitive job market. This community service (PkM) aims to increase the motivation and insight of female students (santriwati) regarding business opportunities in the service sector as an entrepreneurship alternative without requiring significant capital. The main problem faced by the partners in Baturaja was limited business literacy and the perception that entrepreneurship necessitates physical products. The method employed was socialization through interactive lectures, group discussions, and sharing sessions with academics. The results of the activity indicated a significant increase in entrepreneurial motivation among the students, with 85% of participants now expressing interest in starting service-based businesses such as education, design, or digital services. Furthermore, the participants' understanding of practical steps to initiate a business increased substantially. This activity successfully shifted the students' mindset to become more innovative and independent in facing economic challenges post-boarding school education.